Bilingualism in Malaysia: language education policy and local needs - Chan, Swee Heng; Abdullah, Ain Nadzimah (Universiti Putra Malaysia Press, 2015)
On 11 September 2012, the Prime Minister unveiled the National Education Blueprint that laid the foundation for transforming the Malaysian education system. Among the issues addressed was the strengthening of the teaching and learning of the English language alongside the reinforcement of the learning of the national language. Attention was given to ensuring students' English language proficiency through an emphasis on bilingualism (Bahasa Malaysia and English), which is one of the six key "attributes" addressed in the blueprint. The blueprint currently invites comments and feedback from the public in order for it to be sensitive to local needs. In this context, the concept of bilingualism must be clearly established and explained as the degree of bilingual proficiency one achieves often depends on the wider societal attitudes towards the languages concerned. This paper aims to explore the context of bilingualism in Malaysia and to describe responses from an important segment of society, the teachers who contribute to achieving bilingualism among students who ultimately will constitute the workforce of the nation. As such, the policy and current practices have significant implications for any agenda to be successfully implemented in order to contribute meaningfully to local and international economies. The study traces the development of bilingualism and bilingual education in Malaysia. It also provides information on responses of language teachers who are seen to be policy implementers and stakeholders who can provide salient information on the effects related to language education policy.